Cold betrayal [compact disc, unabridged] : an Ali Reynolds novel - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries, 2015)
Ali Reynolds's longtime friend and taser-carrying nun, Sister Anselm, rushes to the bedside of a young pregnant woman hospitalized for severe injuries after she was hit by a car on a deserted Arizona highway. The girl had been running away from The Family, a polygamous cult with no patience for those who try to leave its ranks. Something about her strikes a chord in Sister Anselm, reminding her of a case she worked years before when another young girl wasn't so lucky.